An investigation of the smoking behaviours of parents before, during and after the birth of their children in Taiwan - Shih, Shu-Fang (BioMed Central, 2008)
BACKGROUND: Although many studies have investigated the negative effects of parental smoking on children and Taiwan has started campaigns to promote smoke-free homes, little is known about the smoking behaviours of Taiwanese parents during the childbearing period. To help fill the gap, this study investigated Taiwanese parents' smoking behaviours before, during and after the birth of their children, particularly focusing on smoking cessation during pregnancy and relapse after childbirth. METHODS: We used data from the Survey of Health Status of Women and Children, conducted by Taiwan's National Health Research Institutes in 2000. After excluding survey respondents with missing information about their smoking behaviours, our sample consisted of 3,109 women who were married at the time of interview and had at least one childbearing experience between March 1, 1995 and February 28, 1999. Data on parental smoking behaviour in the six months before pregnancy, during pregnancy, and in the first year after childbirth were extracted from the survey and analysed by descriptive statistics as well as logistic regression. RESULTS: Four percent of the mothers and sixty percent of the fathers smoked before the conception of their first child. The educational attainment and occupation of the parents were associated with their smoking status before the first pregnancy in the family. Over 80% of smoking mothers did not quit during pregnancy, and almost all of the smoking fathers continued tobacco use while their partners were pregnant. Over two thirds of the women who stopped smoking during their pregnancies relapsed soon after childbirth. Very few smoking men stopped tobacco use while their partners were pregnant, and over a half of those who quit started to smoke again soon after their children were born. CONCLUSION: Among Taiwanese women who had childbearing experiences in the late 1990s, few smoked. Of those who smoked, few quit during pregnancy. Most of those who quit relapsed in the first year after childbirth. The smoking prevalence was high among the husbands of these Taiwanese women, and almost all of these smoking fathers continued tobacco use while their partners were pregnant. It is important to advocate the benefits of a smoke-free home to Taiwanese parents-to-be and parents with young children, especially the fathers. The government should take advantage of its free prenatal care and well-child care services to do this. In addition to educational campaigns through the media, the government can request physicians to promote smoke-free homes when they deliver prenatal care and well-child care. This could help reduce young children's health risks from their mothers' smoking during pregnancy and second-hand smoke at home.